UiTM innovation and creativity circle convention / Nurulfalahin Daud @ Ibrahim - Daud @ Ibrahim, Nurulfalahin (Faculty of Pharmacy, 2024)
Innovation and Creativity Circle (CIC/KIK) Convention is an annual event of Universiti Teknologi MARA (UiTM), where each group will present their projects highlighting the innovations and impacts that could be of use to the university. This convention took place in the zone level first and the selected group will bring their projects to the next level of competition in all UiTM branches across the country. This year, the KIK Convention for UiTM Middle Zone was held from October 7th to 8th, 2024 at Dewan Berlian, Puncak Alam Campus.